Art, ritual, and civic identity in medieval southern Italy - Zchomelidse, Nino Maria (The Pennsylvania State University Press, 2014)
"Describes the creation, function, and change in significance of liturgical furnishings and manuscripts in southern Italy from the tenth to the fourteenth centuries"--Provided by publisher